Profil Kondisi Fisik Pemain Sepakbola di Pusat Olahraga Sepakbola (POSBA) Bangsongan - Yozardi, Muhammad Afif; Kurniawan, Wing Prasetya; Zawawi, Anis (Journal of Physical Activity and Sports (JPAS), 2024)
This research is motivated by the uncontrolled physical condition of football players at the Bangsongan Football Sports Center (Posba). This study aims to determine the physical condition of football players at the Bangsongan Football Sports Center (Posba). This research is quantitative descriptive research. The method used is the survey method. The subjects of this study were football players at the Bangsongan Football Sports Center (Posba) totalling 25 people. The instruments used are sit-ups, push-ups, squat jumps, 50 m running test, shuttle run test, vertical jump test, and 15-minute running test. The analysis technique used is pouring the frequency into percentage form. The results of this study indicate that the physical condition profile of football players at the Bangsongan Football Sports Center (Posba) is moderate considering the highest frequency in the mild category with 18 students (75%). The physical condition profile of football players at the Bangsongan Football Sports Center (Posba) is categorized as excellent 0 people (0%,) good 7 people (25%), moderate 18 people (75%), less than 0 people (0%), very less 0 people (0%). Keywords: Physical Condition, Football